Tripeptides derived from reactive centre loop of potato type II protease inhibitors preferentially inhibit midgut proteases of Helicoverpa armigera - Saikhedkar, Nidhi S.; Joshi, Rakesh S.; Bhoite, Ashwini S.; Mohandasan, Radhika; Yadav, Amit Kumar; Giri, Ashok P. (Insect Biochemistry and Molecular Biology, 2018)
Potato type II protease inhibitors (Pin-II PIs) impede the growth of lepidopteran insects by inhibiting serine protease-like enzymes in the larval gut. The three amino acid reactive centre loop (RCL) of these proteinaceous inhibitors is crucial for protease binding and is conserved across the Pin-II family. However, the molecular mechanism and inhibitory potential of the RCL tripeptides in isolation of the native protein has remained elusive. In this study, six peptides corresponding to the RCLs of the predominant Pin-II PIs were identified, synthesized and evaluated for in vitro and in vivo inhibitory activity against serine proteases of the polyphagous insect, Helicoverpa armigera. RCL peptides with sequences PRN, PRY and TRE were found to be potent inhibitors that adversely affected the growth and development of H. armigera. The binding mechanism and differential affinity of the RCL peptides with serine proteases was delineated by crystal structures of complexes of the RCL peptides with trypsin. Residues P1 and P2 of the inhibitors play a crucial role in the interaction and specificity of these inhibitors. Important features of RCL peptides like higher inhibition of insect proteases, enhanced efficacy at alkaline gut pH, longer retention and high stability in insect gut make them suitable molecules for the development of sustainable pest management strategies for crop protection.
Keywords: Helicoverpa armigera; Protease; protease inhibitor; Reactive centre loop peptides